Old Testament quotations in Hebrews: studies in their textual and contextual background - Walser, Georg (Wissenschaftliche Untersuchungen zum Neuen Testament, 2013)
Hauptbeschreibung: Georg A. Walser investigates the use of the Old Testament (Gen. 47:31b; Ps. 40:7b; Jer. 31:33) in the Letter to the Hebrews, taking the complicated textual history of the quotations into account, especially the Septuagint and the possibility that different Hebrew texts may underlie the Greek translation. Further, he draws on the assumption that Hebrews was composed in a Jewish context, where the Old Testament text had been interpreted for a long time. It is also presupposed that this exegesis was handed down in the post Second Temple Jewish community and in the early church